Analysis of State Control Over Natural Resources Oil and Gas (According to Law No. 22 of 2001 Concerning Oil and Gas) - Sibarani, Sabungan (Brawijaya Law Journal, 2018)
Most gas-producing companies are the same foreign companies as oil-producing companies. Investment to produce gas is funded by government banks in industrialized countries. Thus, the exploration and exploitation of natural gas is intended to meet export needs to industrialized countries. Article 33 of the 1945 Indonesian Constitution envisages that the use of natural resources should be prioritized to the maximum extent possible to meet domestic needs and the greatest prosperity of the people. This implies state control over the use of natural resources. It is argued that mining business arrangements, especially Oil and Gas, can be considered as a part of the implementation of state control over natural oil and gas resources. This means that the authority in controlling natural resources of Oil and Gas is only controlled by the State and carried out by the Government as the executor of Oil and Gas business activities. Such arrangement is in accordance with the provisions of Article 4 paragraph (1) and (2) Law No . 22 of 2001 concerning Oil and Natural Gas. This paper analyses the State control over the use of oil and gas as natural resources. The analyses was carried out through the study of the Decision of the Constitutional Court of the Republic of Indonesia Number: 002 / PUU-I / 2003. Using normative juridical approach, this paper argues that the Indonesian Laws on oil and gas are incontrary with the 1945 Indonesian Constitution.